Advances in Information and Computer Security 5th International Workshop on Security, IWSEC 2010, Kobe, Japan, November 22-24, 2010. Proceedings - Echizen, Isao.; Kunihiro, Noboru; Sasaki, Ryoichi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 5th International Workshop on Security, IWSEC 2010, held in Kobe, Japan, in November 2010. The 22 revised full papers presented together with 2 invited talk were carefully reviewed and selected from 75 submissions. The papers are organized in topical sections on encryption, data and web security, protocols, network security, block cipher, and implementation and real life security.
Invited Talks -- Automating Security Configuration and Administration: An Access Control Perspective -- Security Metrics and Security Investment Models -- Encryption -- Publishing Upper Half of RSA Decryption Exponent -- PA1 and IND-CCA2 Do Not Guarantee PA2: Brief Examples -- A Generic Method for Reducing Ciphertext Length of Reproducible KEMs in the RO Model -- An Improvement of Key Generation Algorithm for Gentry$1 (Bs Homomorphic Encryption Scheme -- Data and Web Security -- Practical Universal Random Sampling -- Horizontal Fragmentation for Data Outsourcing with Formula-Based Confidentiality Constraints -- Experimental Assessment of Probabilistic Fingerprinting Codes over AWGN Channel -- Validating Security Policy Conformance with WS-Security Requirements -- Protocols -- Efficient Secure Auction Protocols Based on the Boneh-Goh-Nissim Encryption -- Hierarchical ID-Based Authenticated Key Exchange Resilient to Ephemeral Key Leakage -- Group Signature Implies PKE with Non-interactive Opening and Threshold PKE -- Network Security -- A Generic Binary Analysis Method for Malware -- A-HIP: A Solution Offering Secure and Anonymous Communications in MANETs -- Securing MANET Multicast Using DIPLOMA -- Block Cipher -- Preimage Attacks against Variants of Very Smooth Hash -- Matrix Representation of Conditions for the Collision Attack of SHA-1 and Its Application to the Message Modification -- Mutual Information Analysis under the View of Higher-Order Statistics -- Known-Key Attacks on Rijndael with Large Blocks and Strengthening ShiftRow Parameter -- Implementation and Real Life Security -- Differential Addition in Generalized Edwards Coordinates -- Efficient Implementation of Pairing on BREW Mobile Phones -- Introducing Mitigation Use Cases to Enhance the Scope of Test Cases -- Optimal Adversary Behavior for the Serial Model of Financial Attack Trees.s
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Systems and Data Security; Management of Computing and Information Systems; Data Encryption; Computers and Society; Computer Communication Networks; Algorithm Analysis and Problem Complexity